Comprehensive analysis of codon bias in 13 Ganoderma mitochondrial genomes - Wu, Peng; Xiao, Wenqi; Luo, Yingyong; Xiong, Zhuang; Chen, Xiaodie; He, Jing; Sha, Ajia; Gui, Mingying; Li, Qiang (Frontiers in Microbiology, 2023)
In this study, we investigated the codon bias of twelve mitochondrial core protein-coding genes (PCGs) in 13 Ganoderma strains, three strains of which belonged to G. lucidum and three of which belonged to G. lingzhi. The codons of all Ganoderma strains showed a preference for ending in A/T. Additionally, correlations between codon base composition and the codon adaptation index (CAI), codon bias index (CBI) and frequency of optimal codons (FOP) were identified, demonstrating the impact of base composition on codon bias. Various base bias indicators were found to vary between or within Ganoderma strains, including GC3s, the CAI, the CBI, and the FOP. The results also revealed that the mitochondrial core PCGs of Ganoderma have an average effective number of codons (ENC) lower than 35, indicating strong bias toward certain codons. Evidence from neutrality plot and PR2-bias plot analysis indicates that natural selection is a major factor affecting codon bias in Ganoderma. Additionally, 11 to 22 optimal codons (ΔRSCU>0.08 and RSCU>1) were identified in 13 Ganoderma strains, with GCA, AUC, and UUC being the most widely used optimal codons in Ganoderma. By analyzing the combined mitochondrial sequences and relative synonymous codon usage (RSCU) values, the genetic relationships between or within Ganoderma strains were determined, indicating variations between them. Nevertheless, RSCU-based analysis illustrated the intra- and interspecies relationships of certain Ganoderma species. This study deepens our insight into the synonymous codon usage characteristics, genetics, and evolution of this important fungal group.